Archaeometric characterization and restoration proposal for filling mortars of Oshki (Öşvank) church - Kavali, Evren; Eroğlu, Murat; Çakıcı, Murat; Çakıcı, Fatma Zehra (Springer Science and Business Media LLC, 2023)
Abstract In order to ensure the sustainability of cultural, historical and architectural heritage, preserving and restoring historical buildings and transferring them to future generations is one of the important issues of today. Restoration decisions regarding the repairs of historical buildings are of great importance in this context. Developing correct intervention decisions requires the thorough analysis of the structure, the determination of the structural and material properties meticulously, and the use the most appropriate materials for repairing it. However, only physical and chemical analyses are not sufficient to determine material properties of historical buildings; therefore, archaeometric analyses are needed to determine them more appropriately. In this study, it is aimed to determine the components and characteristics of the filling mortars of Oshki (Öşvank) Church, one of the most magnificent structures of the Eastern Anatolia region, in order to preserve the masonry structure and guide the restoration studies in the light of archaeometric analyses. The raw material properties of the samples taken from the filling mortars of the church were determined by the physical, chemical and petrographic analyses. As a result of the analyses, the aggregate-binding properties of Oshki Church filler mortars were determined. It was revealed that the aggregate content was determined as petrographic, lime was used as a binder and all samples contained pozzolan whereas no cement was used in any of the samples, and the samples did not contain marble rice/powder and organic additives like oil, protein etc. It has also been observed that the aggregate in the mortar content is compatible with the geological formations of near surrounding of the church. In this context, this study emphasizes the importance of archaeometric analysis in restoration of historical buildings. Moreover, differing from other studies in the literature, this study proposes mortar recipe to be used in the restoration of the church, which can pioneer to future studies in the field of architectural restoration.
Keywords: QD71-142; Fine Arts; Petrography; Archaeometric characterization; N; Mortar analysis; Restoration; Oshki church; Material characterization; Analytical chemistry; 11. Sustainability